Evaluating the Urinary Iodine Concentration in Operating Room Personnel After Using Povidone-iodine Hand Scrub - Fateme Karbalai; Farzaneh Jafari; Soheila Bakhtiari (Journal of Holistic Nursing and Midwifery)
Introduction: Studies have shown conflicting results regarding the skin absorption of iodine from povidone-iodine solution (Betadine 7.5%) and its effects on the health of operating room personnel. Objective: This study aimed to measure the urinary iodine concentration (UIC) among the operating room personnel of a hospital in Isfahan, Iran, after using povidone-iodine scrub (Betadine 7.5%). Materials and Methods: This descriptive-analytical study was conducted among operating room personnel of a selected hospital in Isfahan, Iran. Using a convenience sampling method, 100 participants were selected and divided into two groups: Povidone-iodine scrub (n=50) and alcohol-based scrub (n=50). The scrubs were used for one week, three times per day, each for three minutes. One week after the study, morning urine samples were collected to measure the UIC using the Sandell-Kolthoff reaction method. The Shapiro-Wilk test assessed the normality of data distribution, and statistical comparisons between the two groups were conducted using the Mann-Whitney U test and chi-square test. Results: The mean age of the povidone-iodine scrub group and the alcohol-based scrub group were 31.9±6.29 and 31.7±5.59 years, respectively. Also, 94% in the povidone-iodine scrub group and 86% in the alcohol-based scrub group were female. No significant differences were observed between the two groups in age, work experience, gender, educational level, scrubbing frequency, or number of shifts per week. The results showed a significantly higher UIC in the povidone-iodine scrub group compared to the alcohol-based scrub group (290.0±0.73 vs 106.8±27.88 μg/L; P=0.001). Additionally, the prevalence of iodine poisoning (>300 μg/L) was higher in the povidone-iodine group (8% vs 0%; P=0.001). Furthermore, in the povidone-iodine scrub group, the UIC was significantly higher in individuals with hand scrubbing frequency ≥10 per week compared to those with fewer frequency (316.3±54.20 vs 196.5±54.00 μg/L, P=0.001) and in those who worked ≥6 shifts per week (299.3± 66.9 vs 206.2±81.6 μg/L; P=0.011). Conclusion: This study suggests that hand scrubbing with povidone-iodine (Betadine 7.5%) can increase the UIC and the risk of iodine poisoning in operating room personnel. Therefore, it is recommended to consider alternative solutions, such as alcohol-based solutions, for hand scrubbing in operating rooms.